University implements archives record management systems to safeguard alumni details / Anjeli Umbat - Umbat, Anjeli (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The system is designed to provide certain user rights depending on people' academic roles. This guarantees that alumni records are only accessible to authorised persons, such as alumni affairs workers and necessary administrators. The university can retain greater control over the privacy and security of alumni information by matching user permissions with organisational functions.